A prospective study of clinicoepidemiology, metabolic and hormonal profile of women with hirsutism in Konaseema region of Andhra Pradesh - Smitha, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hirsutism is defined as presence of excess coarse hairs appear in male pattern in women.There is various aetiology of hirsutism like Idiopathic hirsutism, PCOS, androgen secreting ovarian tumours, menopause, CAH, Cushing’s syndrome, drugs which increases testosterone level, insulin resistance and tumour secreting androgen. We have designed present study with an aim to study the clinicoepidemiology, metabolic and hormonal profile of women with hirsutism in Konaseema region of Andhra Pradesh. Methods: All patients with hirsutism attending gynaecology outpatient department were selected for study based on inclusion and exclusion criteria. After that patient were examined clinically, BMI was calculated for each patient. Patients were clinically evaluated for signs of excess androgen secretion, Cushing syndrome, metabolic syndrome and hyperprolactinemia. Modified Ferriman-Gallwey scoring system was used for evaluating and quantifying hirsutism. Results: The mean Fasting plasma insulin12.42±2.41 (mIU/dl), the mean of HOMA-IR was 3.14±1.18. The mean value of dehydroepiandrosteronesulphate (DHEAS) 355.78±15.41 mcg/dl. There was statistically significant reduction in modified Ferriman-Gallwey scoring in before and after treatment (12.38± 1.55 vs. 9.62±1.6), the p value was 0.00001. The number of patients with menstrual irregularities were reduced from 63.3% to 20% after treatment and this difference is statistically significant (p=0.04). Conclusions: Hirsutism is associated with insulin resistance and DHEAS concentration was high. Modified Ferriman-Gallwey score was significantly reduced and there was significant weight loss and improvement in menstrual irregularities after treatment.